Views of independent prescribing pharmacists on the community pharmacy pilot independent prescribing service: a qualitative study. (1st April 2022) - Deslandes, R; Mantzourani, E; Hodson, K; Taylor, L
Abstract: Introduction: Independent Prescribing Pharmacists (IPPs) can prescribe autonomously within their scope of practice. Their role is increasing within the community setting (1). The Welsh Pharmaceutical Committee has a vision to have at least one IPP in every community pharmacy by 2030 (1). In 2020, an Independent Prescribers' Service (IPS) pilot was delivered in 13 pharmacies across six of the seven Health Boards in Wales (2), via Choose Pharmacy (CP), an IT platform that provides access to patients' General Practitioner (GP) medical record. IPS allowed patients to access advice, and, where relevant, be treated in the community pharmacy setting, rather than the GP surgery. The consultation is recorded on CP and the patient's GP informed of the outcome. As the IPS is a recent development there is little research on this service. Aim: To explore the views of community IPPs delivering the IPS. Methods: A qualitative methodology was utilised with semi-structured interviews, via telephone or MS Teams. Only thirteen pharmacies were commissioned to deliver the service. Purposive sampling was used to identify IPPs in these premises, who had completed at least one IPS consultation. Participants were informed of the study and written; informed consent obtained. An interview schedule utilised open questions to explore participants' experiences of the service. Interviews were recorded, transcribed and analysed via deductive and inductive thematic analysis. Analysis was quality assured through discussion with the research team. All identifiable information in the transcripts were removed to ensure anonymity. Results: Nine interviews were conducted, including participants from all Health Boards in the pilot. Interviewees had varied prescribing experience with some only prescribing since the roll out of the pilot. The IPPs' scope of practice included acute minor ailments, contraception, urinary tract infections and asthma. Four themes were identified: 1.Impact of the IPS: Participants believed the service had impacted on the wider healthcare setting, patients and themselves. Patients had improved convenience and accessibility to a healthcare professional to manage their condition. Patient safety was of a high standard with access to patient notes ensuring informed, appropriate clinical decisions. 2.Relationship with GP: Positive relationships with local GPs was believed to be critical to the pilot's success. 3.Future delivery: This will rely on support, funding, and ongoing review. A 'blended approach' whereby patients are seen with or without an appointment was believed to provide the flexibility that patients want. 4.Remote consultations: Can have an impact on patient safety, making non-verbal communication and language barriers more challenging. After nine interviews, no new information was gathered. Conclusion: Participants were supportive of the service which will potentially benefit IPPs, patients and GPs, and improve patient care. Pharmacists, by providing a high quality, accessible service, ensures that forward thinking healthcare is delivered in a manner which makes use of the skills of those working in the community. The study, albeit small scale, explored the thoughts of the majority of IPPs conducting the IPS service at that time. More information is needed to understand the impact of the service and effect on practice, from the practitioner and patient perspective. References: (1) Walsh A. All Welsh pharmacies to have independent prescribers. Wales; 2019 [accessed 5 February 2021]. Available from: http://www.pharmacymagazine.co.uk/all-welsh-pharmacies-to-have-independent-prescribers (2) NHS Wales Informatics Service. Choose Pharmacy. Wales; 2021 [accessed 5 Feb 2021]. Available from: http://www.nwis.nhs.wales/systems-and-services/in-the-community/choose-pharmacy/